Comparison of the Effects of Trunk Muscle Training and Cawthorne-Cooksey Training on the Risk of Falls in the Elderly - Isidorus Jehaman; Fenti Fransiska; Redi Tantangan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: The risk of falls in the elderly can lead to serious injuries, making effective prevention strategies essential. Exercises such as trunk muscle exercise and Cawthorne-Cooksey exercise have been shown to be beneficial. Trunk muscle exercise aims to improve core muscle strength and postural stability, while Cawthorne-Cooksey exercise focuses on coordinating head and eye movements to enhance balance. Objective: This study aims to compare the effectiveness of trunk muscle exercise and Cawthorne-Cooksey exercise in reducing fall risk among the elderly. Methods: A quasi-experimental approach was used with a two-group pre-test and post-test design. The sample consisted of two intervention groups: one receiving trunk muscle exercise and the other receiving Cawthorne-Cooksey exercise. Data analysis was conducted using the Wilcoxon test to assess the effectiveness of each intervention and the independent t-test to compare the effects of both exercise methods. Results and Discussion: The Wilcoxon test showed a p-value of 0.046 (? 0.05), indicating that both trunk muscle exercise and Cawthorne-Cooksey exercise were effective in improving balance and reducing the risk of falls in the elderly. However, the independent t-test yielded a p-value of 0.346 (> 0.05), suggesting no significant difference between the two interventions. Despite this, the average improvement in balance scores was higher in the trunk muscle exercise group (mean difference of 1.444) compared to the Cawthorne-Cooksey group (mean difference of 1.222). Conclusion: The findings